2D Materials: Fractal‐Theory‐Based Control of the Shape and Quality of CVD‐Grown 2D Materials (Adv. Mater. 35/2019). Issue 35 (26th August 2019) - Li, Junzhu; Chen, Mingguang; Zhang, Chenhui; Dong, Haocong; Lin, Weiyi; Zhuang, Pingping; Wen, Yan; Tian, Bo; Cai, Weiwei; Zhang, Xixiang
Abstract : In article number 1902431, Bo Tian, Weiwei Cai, Xixiang Zhang, and co‐workers reveal the existence of a fractal‐growth‐based mechanism in 2D‐material chemical vapor deposition (CVD) syntheses. Based on a 2D diffusion‐limited aggregation model, perfect correlations between theoretically simulated data and CVD experimental results are obtained. Eventually, the precise control of 2D‐material shapes and qualities is achieved by adjusting single‐domain net growth rates in the CVD‐growth process.